In Defence of Type-A Materialism (Diametros, 2016)
In this paper, I argue against the phenomenal concept strategy (henceforth PCS) and in favor of what Chalmers has called type-A materialism (2006; 2010: 111). On her release, Mary makes no cognitive discovery at all; not even a thin non-possibility-eliminating discovery, as Tye has recently claimed (2012). When she is imprisoned, Mary already knows everything that is to be known about the phenomenal character of her experiences. What Mary acquires is a new non-cognitive and nonconceptual representation.